Gaya Bahasa Prinsip Dakwah dalam Al-Quran dan Kaitannya dengan Moderasi Beragama (Analisis Linguistik Surah An-Nahl 125) - Abdul Kosim (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to determine the style of language of the principles of da'wah in Surah An-Nahl verse 125, the concept of religious moderation according to the Ministry of Religion of the Republic of Indonesia and how the two are related. The results of this study concludes that there are three interrelationships, namely 1. The principle of Wisdom (al-Hikmah) gives birth to a reflection language style (Istifham) and realizes the value of tolerance (at-Tasamuh); 2. The principle of good advice (al-Mau'idzhah al-Hasanah) gives birth to a dialogue style (Hiwar) and realizes democratic values (asy-Syuuroo); 3 Principles of Plenary Argument (al-Mujadalah bi al-Husna) gives birth to an analogy language style (Amtsal) and realized the value of proportion (al-I'tidal).